Dreamt I found you : a novel - Han, Jimin (Novelist) (Little, Brown and Company, 2026)
"When Dahee Shin was nine years old, she made a promise to protect her favorite cousin, Channing, who has always been like a sister to her. Now, at thirty, Dahee has found herself in a Korean American community in a New England beach town, once more running to the rescue of her debt-ridden relative. Ever the idealist, Channing--who has spent her life haunted by the tragic story of Chunhyang and Mongryong, Korea's parallel Romeo & Juliet--has fallen in love with Minjae Oh, all the while fending off the advances of powerful, manipulative Kent Cho, a local politician. As Channing and Minjae's romance blossoms, and as Kent's suspicion and obsession grow, Dahee begins to realize that it may be up to her to make sure her cousin and beloved escape Chunhyang and Mongryong's doomed end."--Amazon